HUBUNGANINFORMASI TENTANG SMK DENGAN MINAT SISWA SMP MEMILIH PROGRAM KEAHLIAN TATA BOGA DI KABUPATEN PESISIR SELATAN - Jefriyanti, Ranti; Elida, Elida; Faridah, Anni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The purpose of this study to analyze the relationships of information about vocational interests junior high school students choose skill program Culinary. This research is a quantitative correlation approach. This study population junior class IX students at the Kabupaten Pesisir Selatan academic year 2016/2017, amounting to 7,700 students with a sample of 192 students. The sampling technique by means of cluster sampling.Collecting data using a questionnaire with Likert scale and Gutman scale.The data is processed using SPSS 16. The results of this study concluded that there is a positive relationship and significant information about vocational interests junior high school students choose skill program Culinary to the count r ie: 0237 with the interpretation of the relationship is lowKey Word: information, vocational school, interest junior high school student, culinary